Determining the correlations between faculty of sport sciences students’ unemployment anxiety and their levels of hopelessness - Mine Koc (ROL Spor Bilimleri Dergisi)
This study to determine the correlations between sport sciences students’ anxiety about unemployment and their levels of hopelessness.  The study group was composed of 258 students in total 167 of whom were male and 91 of whom were female who attended the sport sciences faculty of Adıyaman University in 2021-2022 year. “Unemployment Anxiety Scale” and “Beck Hopelessness Scale” were used to collect research data. According to the results obtained, while the unemployment anxiety levels of the students showed a significant difference in the demographic variable according to their grade point averages (p<0.05), there was no difference in Beck hopelessness levels according to their age and general grade averages (p>0.05). As a result of the correlation analysis, a positive, moderate and significant relationship was found between unemployment anxiety and hopelessness in general (p<0.05). As a result, it has been found that all sub-factors of unemployment anxiety have an increasing effect, except for the contraction in employment and the decrease in the workforce. Therefore, it can be said that students' grade point averages and ages are significant variables in unemployment anxiety and/or hopelessness.